Quantitative analysis of tegmen bone mineral density in obese and non-obese patients. Issue 12 (1st December 2021) - Holmes, S; Geimadi, A; Mamilly, A; Hamiter, M; Cuellar, H; Mankekar, G
Abstract: Background: Certain factors have been linked to lateral skull base demineralisation or erosion, which may predispose to spontaneous cerebrospinal fluid leak. There are relatively few quantitative reports of skull base changes in patient populations. Method: A novel refined measurement algorithm for quantification of tegmen bone mineral density was developed, and bone mineral density between obese and non-obese patient groups was compared. Computed tomography scans were analysed by three blinded reviewers, and tegmen bone mineral densities were compared. Results: There were 23 patients in the obese group and 27 matched controls in the non-obese group. Inter-rater reliability was 'strong' to 'near complete' (κ = 0.75–0.86). No differences in tegmen bone mineral density were found between the groups ( p = 0.64). The number of active blood pressure medications correlated positively with lateral skull base bone mineral density. Conclusion: A novel, refined, quantitative measurement algorithm for the assessment of tegmen bone mineral density was developed and validated. Obesity was not found to significantly affect tegmen bone mineral density.